2004
DOI: 10.1086/421747
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Observations and Analysis of the Peculiar SN 1999aa

Abstract: We present an extensive new time-series of spectroscopic data of the peculiar SN 1999aa in NGC 2595. Our data set includes 25 optical spectra between -11 and +58 days with respect to B-band maximum light, providing an unusually complete time history. The early spectra resemble those of a SN 1991T-like object but with a relatively strong Ca H&K absorption feature. The first clear sign of Si II 6355, characteristic of Type Ia supernovae, is found at day -7 and its velocity remains constant up to at least the fir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 88 publications
(140 reference statements)
13
85
0
Order By: Relevance
“…The SYNOW fit of SN 2008ha is similar to those of the −1 and −5 days spectra of SNe 2002cx (Branch et al 2004) (Phillips et al 2007), SN 1999aa, a slightly over-luminous SN Ia (Garavini et al 2004), SN 2006gz, a luminous SN Ia with C features in its pre-maximum spectra (Hicken et al 2007), SN 2004aw, a SN Ic that was originally classified as a SN Ia (its true nature was only realized with nebular spectra; Taubenberger et al 2006), and SN 2007gr, a well-observed SN Ic with a spectrum somewhat similar to SN 2004aw (Valenti et al 2008). The maximum-light spectrum of SN 2008ha is generally similar to all five comparison spectra after correcting for velocity differences.…”
Section: Maximum-light Spectrumsupporting
confidence: 70%
“…The SYNOW fit of SN 2008ha is similar to those of the −1 and −5 days spectra of SNe 2002cx (Branch et al 2004) (Phillips et al 2007), SN 1999aa, a slightly over-luminous SN Ia (Garavini et al 2004), SN 2006gz, a luminous SN Ia with C features in its pre-maximum spectra (Hicken et al 2007), SN 2004aw, a SN Ic that was originally classified as a SN Ia (its true nature was only realized with nebular spectra; Taubenberger et al 2006), and SN 2007gr, a well-observed SN Ic with a spectrum somewhat similar to SN 2004aw (Valenti et al 2008). The maximum-light spectrum of SN 2008ha is generally similar to all five comparison spectra after correcting for velocity differences.…”
Section: Maximum-light Spectrumsupporting
confidence: 70%
“…We have identified two SN Ia in our sample showing strong similarities with the spectra of SN 1999aa (Garavini et al 2004) (see Fig. 5).…”
Section: Peculiar Sn Iasupporting
confidence: 57%
“…Our SN templates are from Peter Nugent's spectral library 50 (see Nugent et al 2002, and the SUSPECT database; 51 1954A, 1962L, 1964L, 1990B, 1990I, 1994I, 1998bw, 1999ex, 2000H, 2002ap II 1948B, 1959D, 1961F, 1961I, 1961V, 1964F, 1964H, 1969L, 1970A, 1986E II 1987A, 1988A, 1988H, 1988Z, 1989C, 1990ae, 1990ag, 1990E, 1990H, 1990K II 1990Q, 1990V, 1990X, 1991C, 1991H, 1991J, 1992aa, 1992ab, 1992C, 1992H II 1993J, 1994aj, 1996L, 1997ab, 1997cy, 1997D, 1998dn, 1998S, 1999em, 2004dj Ia-pec 1957A, 1960H, 1986G, 1991bg, 1991bj, 1991F, 1991T, 1997br, 1997cn, 1999aa Ia-pec 1999ac, 1999by, 2000cx Nugent's Branch-normal (Branch et al 1993), SN 1991T-like (e.g., Filippenko et al 1992a), and SN 1991bg-like (e.g., Filippenko et al 1992b) templates (supplemented by spectra of some peculiar SNe Ia (e.g., SN 1999aa, Garavini et al 2004;SN 1999by, Garnavich et al 2004 from SUSPECT. For SNe Ib/c, the templates used are Nugent's normal SN Ib/c and hypernova spectra, as well as observed spectra of SN 1990B (Matheson et al 2001), SN 1990I (Elmhamdi et al 2004), SN 1994I (Clocchiatti et al 1996), SN 1998bw (Ferdinando et al 2001), SN 1999ex (Hamuy et al 2002), SN 2000H (Branch et al 2002), and SN 2002ap (Gal-Yam et al 2002, from the SUSPECT database).…”
Section: Cross-correlation Analysismentioning
confidence: 99%